Care and the politics of shame: Medical practitioners and stillbirths in a South African district hospital. Issue 4 (2nd October 2019) - Lappeman, Maura; Swartz, Leslie
Abstract : Research into the abuse of women during childbirth has increased over recent years. Many studies have focussed on labouring women, how they may be physically maltreated, neglected, or shouted at, and on how their needs are unmet by healthcare practitioners. As part of a larger study focussing on staff responses to stillbirths, we wanted to focus our attention on how medical doctors, working in a district hospital in an impoverished urban setting in the Western Cape Province of South Africa, manage, and feel regarding, stillbirths. This healthcare system experiences an immense patient load, with the poverty of the community it serves, and the numerous traumas, affecting both patients and staff. In order to obtain rich exploratory data, a qualitative research methodology was used. The primary data source was interviews with medical doctors regarding their practices with women who have stillbirths. From the interviews, previous findings about this topic are corroborated by our work within the hospital. Additionally, we include and discuss new findings that we discovered in our research, such as frustrations in communication, feeling culturally different, feeling overwhelmed and shame. From our findings we can conclude that dealing with stillbirth is emotionally challenging anywhere in the world, however, in a context like South Africa, there is the added burden of trying to right the wrongs of a brutal and divided society. These medical doctors are dealing not only with stillbirths but also, to a degree, with the stillbirth of the hope that, twenty-five years after becoming a democracy, South Africa is far from becoming a unified and caring society. There is a great irony, of course, in the fact that we see in the data here the re-enactment of dehumanising discourses by the very people who are working very hard to restore humanity in a fractured society. It would be easy simply to condemn these dehumanising, detaching and discriminatory statements and practices. To do so, we believe, would be defensive in itself – for change to occur, we need to understand the complex personal and political roots of what health practitioners do to survive under very difficult circumstances.